2005
DOI: 10.1007/s10162-005-0012-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Partially Differentiated Mouse Embryonic Stem Cells in the Scala Media of the Guinea Pig Cochlea

Abstract: The low regenerative capacity of the hair cells of the mammalian inner ear is a major obstacle for functional recovery following sensorineural hearing loss. A potential treatment is to replace damaged tissue by transplantation of stem cells. To test this approach, undifferentiated and partially differentiated mouse embryonic stem (ES) cells were delivered into the scala media of the deafened guinea pig cochlea. Transplanted cells survived in the scala media for a postoperative period of at least nine weeks, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 47 publications
1
70
1
4
Order By: Relevance
“…Although we did identify a small number of ESCs in the scala media 2 weeks after transplantation, most of these cells were dead or dying based on morphological evidence of apoptosis. Another recent study has reported that partially differentiated mouse ESCs can survive in the endolymphatic space after transplantation into scala media of the guinea pig (Hildebrand et al 2006). A likely explanation for the ability of any cells to survive in the scala media is disruption of the normal tight-junction barrier between endolymph and perilymph by injection trauma.…”
Section: Esc Survival Is Much Greater In Perilymph Than In Endolymphmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did identify a small number of ESCs in the scala media 2 weeks after transplantation, most of these cells were dead or dying based on morphological evidence of apoptosis. Another recent study has reported that partially differentiated mouse ESCs can survive in the endolymphatic space after transplantation into scala media of the guinea pig (Hildebrand et al 2006). A likely explanation for the ability of any cells to survive in the scala media is disruption of the normal tight-junction barrier between endolymph and perilymph by injection trauma.…”
Section: Esc Survival Is Much Greater In Perilymph Than In Endolymphmentioning
confidence: 99%
“…Potential cell sources for inner ear transplantation include fetal dorsal root ganglion cells (Hu et al 2004;Regala et al 2005), neural progenitor cells (Ito et al 2001;Corrales et al 2006;), stem or progenitor cells isolated from inner ear (Li et al 2003a;Doetzlhofer et al 2004;Rask-Andersen et al 2005;Zhai et al 2005), immortalized auditory neuroblast cells (Nicholl et al 2005;Liu et al 2006a, b), ESCs and their derived neuronal cells (Li et al 2003b;Hu et al 2004Hu et al , 2005Hildebrand et al 2006;Okano et al 2005;Regala et al 2005;Coleman et al 2006;Sakamoto et al 2004;Sekiya et al 2006;Corrales et al 2006), and marrow stromal cells treated with sonic hedgehog and retinoic acid (Kondo et al 2005). ESCs derived from the inner cell mass of the blastocyst are capable of undergoing an unlimited number of divisions and differentiating into cell types of all three germ layers.…”
Section: Introductionmentioning
confidence: 99%
“…They have also shown that neural progenitors derived from mouse embryonic stem cells can integrate into a damaged cochlear nerve and send out neural processes toward the cochlea (Corrales et al, 2006). Several other groups have explored the use of mouse embryonic stem cells, bone marrow cells, or neural stem cells for repopulation of the cochlear nerve, organ of Corti, and lateral cochlear wall (Hildebrand et al, 2005;Lang et al, 2006;Matsuoka, Kondo, Miyamoto, & Hashino, 2006;Matsuoka, Kondo, Miyamoto, & Hashino, 2007).…”
Section: Stem Cell Transplantationmentioning
confidence: 99%
“…Die transplantierten Zellen konnten sogar noch nach mehreren Wochen im Innenohr nachgewiesen werden [6]. Kürzlich ist berichtet worden, dass die Zellen sich 9 Wochen nach Transplantation in der Scala media nachweisen ließen, allerdings ist es zu keiner Integration ins Corti-Organ gekommen, deshalb konnte auch keine Hörver-besserung im transplantierten Ohr im Vergleich zur unbehandelten Gegenseite nachgewiesen werden [4]. Obwohl wir in dieser Arbeit keine Daten über eine Integration der Vorläuferzellen ins Corti-Organ der Mäuse haben, halten wir dies eher für unwahrscheinlich.…”
Section: Diskussionunclassified